Analysis of Zig-Zag Gas Inlet Design Effectiveness to The Reduction of CO2 and H2S Gas at Purifier Equipment using Four Absorber Types - Ridh Hantoro; Hari Firnanda; Sarwono Sarwono (IPTEK Journal of Proceedings Series, 2018)
Design of inlet gas in purifier equipment was affected on the reduction of CO2 and H2S.This study has been conducted on the analysis of the effect of zig-zag gas inlet design on the level of CO2 and H2S gas reduction in purifier using 4 types of absorber. Ferrioxide, iron gram, limestone (CaO), and natural zeolite were used as absorber material. The objective of this research is to determine which the most effective type of absorber in reducing CO2 and H2S gas and create an economical and useful purifier equipment for society. The results was found that the natural zeolite absorber was an effective absorber in reducing CO2 gas, CO2 content before purification was 40.98 % and after purification was 25.80 %, decreasing of CO2 was 15.18 %. Meanwhile, ferrioxide absorber, iron gram and CaO was not effective in reducing CO2. Ferrioxide was found to be effective absorber in reducing H2S, average decreasing was 16.95 ppm. Average decreasing of H2S in natural zeolite and iron gram absorber were 2.13 ppm and 0.16 ppm, respectively. CaO was found to be ineffective absorber for H2S due to increasing in H2S levels after purification.